ANALYZING PODCAST APPLICATION TO IMPROVE LISTENING ABILITY - Widi Rafidah Agarid; Maulida Nurzahra (PROJECT (Professional Journal of English Education), 2018)
The aim of this research is to find out whether Podcast Applications (learning english-free english podcast listening application) that was released by the British Council, will help to improve listening ability. While listening to the episode, on screen will appear script that what student listen. It is make listeners to know what discussed in it. The purpose of the use of this application is that the student can improve listening ability with continuous listening and getting used to being in an English environment.This research is qualitative research with case study method. The research finding showed that podcast application could improve student ability. After heard the podcast, the students could understand, received and respond the speakers of the application.  It is indicates that the application is very useful for learning English especially in listening ability with an easier way and in accordance in this era.